Corruption Risks in Renewable Resource Governance: Case Studies in Iceland and Romania - Gisladottir, Johanna (2020)
In this research, we attempt to shed light on the question of where corruption risks in the governance of renewable resources are located and how they have been addressed in European countries that have different levels of corruption. A comparative case study design was chosen, looking into the fisheries sector in Iceland and the forestry sector in Romania. We conducted 25 semi-structured interviews with various stakeholders sampled through a snowball method. Qualitative coding and systems analysis were used to analyse the interviews. The results indicate that comprehensive and ambitious legislation does not necessarily translate into successful resource governance systems. In general, the institutions that were put in place to enforce and monitor the legal codes and regulations did not have the capacity to carry out their role. Additionally, interviewees were generally found to have a widespread perception of there being a corrupt relationship between politics and big companies operating in their sectors. Our findings suggest that when people hold such perceptions, it undermines anti-corruption policy efforts in the resource sectors, which can then impede sustainable resource management.